Libraries and open access: the implications of open-access publishing and dissemination for libraries in higher education institutions - Pinfield, Stephen (Springer, 2007)
This chapter discusses the consequences of open-access (OA) publishing and dissemination for libraries in higher education institutions (HEIs). Key questions (which are addressed in this chapter) include: